Causes and effects of contract management problems: Case study of road construction - Hanák, Tomáš; Vítková, Eva (Frontiers in Built Environment, 2022)
Contract management is a crucial component of any project. As construction projects are complex and difficult to manage, adequate attention must be given to the related contract management issues. Inexpert management can bring about serious unfavourable consequences that can even result in a project failure. This study aims to explore a specific case study: a private road construction project implemented in the Czech Republic. The analysis consists in identifying potential problems and discussion of their implications. The problem is investigated on three levels: economic, technical and legal. The paper also considers contrasting attitudes of the contracting parties (buyer and supplier), e.g. from the point of view of the causes of problems. Several recommendations are formulated on the basis of the research findings. The results of this study have an ambition to improve contract management capabilities in the construction sector in order to prevent the occurrence of similar problems in future and contribute to our understanding of long-term effects of contract management problems throughout the life cycle.